Penerapan Metode Eigenface Untuk Pencocokan Wajah Dengan Menggunakan Scale Invariant Feature Transform - Halawa, Elisabet Noferia (Jurnal Kajian Ilmiah Teknologi Informasi dan Komputer, 2023)
The problem in this study is matching face objects to recognize a person's identity that can be used in the field of data security, so to secure a data is encoded by using a facial image so that data access is maintained from parties who do not need to access it. One solution to the problems described above is to apply a method that can recognize the sutu object. One method that is often used is Invariant Feature Transform (SIFT). Scale Invariant Feature Transform (SIFT) is a method for detecting and describing local features in an image. The author did not find the same Title of the previous study, but the author found the previous research using the same method among others. From the results obtained in table 4.1, this method is able to identify faces by comparing keypoint values, where as in step 7 the keypoint obtained against the previous sample image only has 2 keypoints produced, where the sample face image has 64 keypoints while the results obtained on the test image have 66 keypoints.